Hydrogel micromotors with catalyst-containing liquid core and shell. (21st March 2019) - Zhu, Hong; Nawar, Saraf; Werner, Jörg G; Liu, Jinrun; Huang, GaoShan; Mei, YongFeng; Weitz, David A; Solovev, Alexander A
Abstract: Methacrylic anhydride-derived hydrogel microcapsules have unique properties, including reversibly tunable permeation, purification, and separation of dissolved molecular species. Endowing these dynamic encapsulant systems with autonomous motion will significantly enhance their efficiency and applicability. Here, hydrogel micromotors are realized using complex water-in-oil-in-water double emulsion drops and oil-in-water emulsion drops from glass capillary microfluidics and subsequent photopolymerization. Three hydrogel micromotor strategies are explored: microcapsules with thin shells and liquid cores with dispersed catalytic Pt nanoparticles, as well as water-cored microcapsules and homogeneous microparticles selectively coated with Ti/Pt catalytic layers. Autonomous motion of hydrogel particles and capsules is realized in hydrogen peroxide solutions, where generated oxygen microbubbles propel the dynamically responsive micromotors. The micromotors are balanced by weight, buoyancy, lateral capillary forces and show specific autonomous behaviours that significantly extend short range dynamic responses of hydrogels. Drop-based microfluidics represent a paradigm shift in the integration of multifunctional subsystems and high-throughput design of chemical micromachines in reasonable quantities towards their desired biomedical, environmental and flow/diffusion microreactor applications.